2010
DOI: 10.1016/j.jpainsymman.2009.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Paraneoplastic Raynaud's Phenomenon—Good Palliation After a Multidisciplinary Approach

Abstract: Paraneoplastic Raynaud's phenomenon is a rare complication of a number of different malignancies (carcinomas, sarcomas, lymphomas, and leukemias). We present a case of paraneoplastic Raynaud's phenomenon in a patient with non-small-cell lung cancer that was associated with significant morbidity, involved a multidisciplinary approach, and eventually responded to a specialized intervention (i.e., iloprost trometamol).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…Paraneoplastic causes are rarely reported - 68 cases in Guigne's study and 33 cases in Schildmann's study - it is often a pulmonary, mammary, uterine, or ovarian site [ 1 - 2 ]. The dominant histological type is adenocarcinoma [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Paraneoplastic causes are rarely reported - 68 cases in Guigne's study and 33 cases in Schildmann's study - it is often a pulmonary, mammary, uterine, or ovarian site [ 1 - 2 ]. The dominant histological type is adenocarcinoma [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various prior case-reports have demonstrated that treatment of the malignancy also causes improvement with regards to the paraneoplastic Raynaud’s phenomenon 6 15 24…”
Section: Discussionmentioning
confidence: 99%
“…Также следует отметить, что феномен Рейно выделяют в составе паранеопластического синдрома. В ряде исследований появление симптомов феномена Рейно свидетельствует об активности онкологического процесса [25,26]. Однако у части пациентов с первичным паранеопластическим процессом развивается склеродермоподобный синдром уже после диагностики онкологического процесса, что, в свою очередь, свидетельствует о роли специфической терапии онкологических заболеваний в возникновении системной склеродермии.…”
Section: феномен рейноunclassified